2023
DOI: 10.3390/biomedicines11123266
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Understanding and Classifying Chronic Orofacial Pain: Key Insights from Biopsychosocial Models and International Classifications (ICHD-3, ICD-11, ICOP)

Federica Canfora,
Giulia Ottaviani,
Elena Calabria
et al.

Abstract: In exploring chronic orofacial pain (COFP), this review highlights its global impact on life quality and critiques current diagnostic systems, including the ICD-11, ICOP, and ICHD-3, for their limitations in addressing COFP’s complexity. Firstly, this study outlines the global burden of chronic pain and the importance of distinguishing between different pain types for effective treatment. It then delves into the specific challenges of diagnosing COFP, emphasizing the need for a more nuanced approach that incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 142 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Preclinical research, including in vitro and in vivo studies, can provide invaluable data that are not feasible to investigate in humans [ 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. This study showed that the incorporation of the C-3 side chain elicits subtle differences in curiosity and emotion in animal models of motor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical research, including in vitro and in vivo studies, can provide invaluable data that are not feasible to investigate in humans [ 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. This study showed that the incorporation of the C-3 side chain elicits subtle differences in curiosity and emotion in animal models of motor function.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the incorporation of the C-3 side chain elicits subtle differences in curiosity and emotion in animal models of motor function. Ongoing clinical studies have advanced our understanding of the behavioral domains in neuropsychiatric conditions and have sought their potential management [ 184 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 ]. Furthermore, computational strategies accelerate our advancement in comprehending their pathology, as well as in developing novel strategies for the management of neurological and psychiatric disorders, including neurotropic computer-assisted drug design [ 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ].…”
Section: Discussionmentioning
confidence: 99%